Evaluation of the thermal comfort for its occupants inside a vehicle during summer. (September 2019) - Danca, P; Nastase, I; Bode, F; Croitoru, C; Dogeanu, A; Meslem, A
Abstract: Thermal comfort of occupants from the vehicle environment has gained more importance in the last decades because time spent by people in the vehicles is increasing. During each trip, driver's thermal comfort must to be ensured to reduce both thermal stress (thus reduces the risk of accidents) and for a healthy state of the occupants. Given the fact that the vehicle environment is non-uniform and fast transient, and because the actual standard (ISO 14505) proposes comfort evaluation methods developed for the steady state conditions in buildings, the purpose of the study is to evaluate a vehicle environment using the three standardised method presented in the above standard. All the three standardized evaluation indices were achieved through standardised methods. The equivalent temperature ( teq ) index was assessed with an advanced thermal manikin and its values were compared with the survey answers given by people in questionnaires (TSV Thermal Sensation Vote index) and with Predicted Mean Vote (PMV) index values calculated with Comfort Sense standardized evaluation equipment. A first conclusion is that the results of the three evaluation indices are different. Air temperature is different from a zone of the car to another and the thermal evaluation must be done in the place of each passenger.